Determinants of theemergence and the development of clusters = Determinanty powstania i rozwoju klastrów - Piątyszek-Pych, Alina (Zielona Góra: Faculty of Economics and Management Press)
The aim of this article is to systemize the most important concepts defining determinants of functioning of cluster structures. The achievement of such formulated goal required carrying out a thorough review of both Polish and foreign literature on the issue of bunches. Due to the volume restrictions of this article, there were presented only the selected, according to the author most interesting, concepts associated with the issues of success factors of bunches. The author?s attention was focussed on the analysis of the factors determining the success of any cluster at the stage of its creation (the determinants of the emergence and creation of bunches) and of its development (determinants of functioning).
Keywords: klastry; czynniki sukcesu gron; źródła przewagi konkurencyjnej lokalizacji; clusters; success factors of bunches; sources of the competitive edge of the location